Electronic stopping power calculation for water under the Lindhard formalism for application in proton computed tomography - Guerrero, A. F.; Mesa, J. [UNESP] (AIP Publishing, 2016)
Because of the behavior that charged particles have when they interact with biological material, proton therapy is shaping the future of radiation therapy in cancer treatment. The planning of radiation therapy is made up of several stages. The first one is the diagnostic image, in which you have an idea of the density, size and type of tumor being treated; to understand this it is important to know how the particles beam interacts with the tissue. In this work, by using de Lindhard formalism and the Y.R. Waghmare model for the charge distribution of the proton, the electronic stopping power (SP) for a proton beam interacting with a liquid water target in the range of proton energies 101 eV - 1010 eV taking into account all the charge states is calculated.